The Effect of British Council for Teens Website on Students’ Vocabulary at the Tenth Grade Students of SMAN-1 Palangka Raya - Arga Syafutra; Bahing; Olga Dona Retsi; Ristati; Muhammad Subhan Fikri (The Study Program of English Education of Palangka Raya University, 2023)
English vocabulary is crucial. However, students struggled with vocabulary. This study examined how the British Council for Teens website affected Senior High School tenth-graders’ English vocabulary. This website taught English vocabulary using topic-related graphics and audio. This pre-experimental investigation used a one-group pre- and post-test. The researcher used purposive sampling to choose the SMAN-1 Palangka Raya X-6 class. Data was collected via a short answer test. Pre- and post-tests were provided. The researcher circulated a questionnaire to assess the British Council for Teens website’s impact on vocabulary learning. The Paired Sample T-Test in SPSS version 25 was used to examine the data at 5% (0.05). T-test analysis accepted Ha and rejected Ho. Hence, British Council for Teens improved SMAN-1 Palangka Raya tenth graders’ English vocabulary. The British Council for Teens website’s favorable questionnaire result supported that. Consequently, this website was effective on expanding students’ English vocabulary.